2020
DOI: 10.1007/s11469-020-00363-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shinrin-Yoku (Forest Bathing) and Nature Therapy on Mental Health: a Systematic Review and Meta-analysis

Abstract: Shinrin-yoku, immersing oneself in nature using one's senses, has been receiving increased attention internationally. While most of the existing studies have focused on physical health, this systematic review and meta-analysis examined the mental health impacts of shinrin-yoku, using the PRISMA guidelines (PROSPERO registry: BLINDED). Of 497 articles retrieved on databases including PubMed/MEDLINE, PsycINFO, Science Direct and Google Scholar, twenty met the inclusion criteria. All studies were conducted in Asi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
167
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(182 citation statements)
references
References 61 publications
12
167
0
3
Order By: Relevance
“…This near-universal finding supports that natural environments are generally enjoyed more than urban ones. Our data are consistent with prior findings of nature's beneficial effects compared to urban environments (Bielinis et al, 2018;Doimo, Masiero & Gatto, 2020;Hansen & Jones, 2020;Kotera, Richardson & Sheffield, 2020;Park et al, 2011).…”
Section: Notessupporting
confidence: 93%
See 1 more Smart Citation
“…This near-universal finding supports that natural environments are generally enjoyed more than urban ones. Our data are consistent with prior findings of nature's beneficial effects compared to urban environments (Bielinis et al, 2018;Doimo, Masiero & Gatto, 2020;Hansen & Jones, 2020;Kotera, Richardson & Sheffield, 2020;Park et al, 2011).…”
Section: Notessupporting
confidence: 93%
“…City living impacts mental health negatively and contributes to increased amygdala activity, negative affect, stress, mood and anxiety disorders (Diorio, Viau & Meaney, 1993;Lederbogen et al, 2011;Peen et al, 2010) whereas exposure to green spaces has been found to be protective (Tost et al, 2019). Extensive research into green spaces and forest bathing demonstrates their stress-reducing effects and their potential to foster physical and mental healing (Bielinis et al, 2018;Doimo, Masiero & Gatto, 2020;Hansen & Jones, 2020;Kotera, Richardson & Sheffield, 2020;Park et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Four of these were conducted in Korea and one each in Japan, Australia, Indonesia, Italy, the USA, China, and the UK. Three included papers were systematic reviews with additional meta-analyses [ 27 , 28 , 29 ]. Most of the reviews examined the effects of forest-based interventions for specific indications, such as stress or depression [ 27 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three included papers were systematic reviews with additional meta-analyses [ 27 , 28 , 29 ]. Most of the reviews examined the effects of forest-based interventions for specific indications, such as stress or depression [ 27 , 29 , 30 , 31 , 32 , 33 , 34 ]. Three studies are broader in scope and examined the health effects of forest-based interventions without focusing on specific conditions [ 19 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation